Ordinary People and Emotional Expression in Dutch Public Service News - Pantti, Mervi; Husslage, Karin (Javnost-The Public, 2009)
In news broadcasts, there is a growing tendency to rely on the voices of ordinary people in comparison with official voices, such as media professionals and experts. In our study, which is based on a quantitative and qualitative content analysis and interviews with journalists, we look at the vox pops on the Dutch public service newscast, NOS News. This article addresses questions of how ordinary people take part in public discussion - what kind of views and emotions they express – and how journalists assess the quality of the vox pops and the emotional expression they include. Our study is discussed in the context of citizen participation in public life through the mass media, the emotionalising of news journalism and the crisis of public service broadcasting. We suggest that the emotional dimension of news, exemplifi ed in the vox pops interviews, should be examined in terms of its potential to foster passions and identities that connect people with public life and with each other.